Description of Emotion Regulation of Hwdi Leaders Who Experience Physical Limitations - Sholahuddin Yusuf Al Mauludi; M Fahmi Aufar Asyraf; M Fahmi Aufar Asyraf (International Conference on Sustainable Health Promotion, 2025)
This study aims to describe emotion regulation among leaders of the Indonesian Women with Disabilities Association (HWDI) with physical impairments. The background of this research lies in the emotional challenges often faced by leaders with disabilities in carrying out leadership roles, where emotion regulation plays a crucial role in maintaining psychological well-being and organizational effectiveness. A qualitative approach with a phenomenological design was employed, involving three respondents selected through purposive sampling. Data were collected using a semi-structured interview guide focusing on two dimensions of emotion regulation: cognitive reappraisal and expressive suppression. The results indicate that cognitive reappraisal was applied through strategies such as viewing situations positively, recalling pleasant experiences, planning flexible steps, and adopting others’ perspectives, while expressive suppression was performed by controlling facial expressions, regulating breathing rhythm, practicing brief meditation, listening to music, diverting attention, and seeking a comfortable environment. These findings suggest that cognitive reappraisal is more adaptive in reducing stress and enhancing social relationships, whereas expressive suppression is useful in maintaining self-image but may cause internal pressure.